Princípios teórico-conceituais e metodológicos da educação interprofissional em saúde: uma revisão de escopo - Alves, Keislyane Ketlyn (Universidade Federal de São Carlos, 2025)
This study aimed to identify and synthesize scientific evidence on the theoretical-conceptual and methodological assumptions of Interprofessional Health Education. It is a Scoping Review following the methodological framework of the Joanna Briggs Institute. The question was: What are the theoretical-conceptual and methodological assumptions of Interprofessional Health Education? The searches were conducted in the following databases: Medline/OVID, LILACS, ERIC, Scopus and Web of Science. Included were theoretical studies, literature reviews that used double-blind identification of research in the databases, primary and secondary empirical studies, quantitative, qualitative and mixed, published in Portuguese, English and Spanish, without a time limit. The titles, abstracts and full texts were analyzed by two reviewers and conflicts were resolved by a third reviewer. A total of 768 documents were obtained, of these, 14 were included in this review. There was a predominance of literature review studies from the United States, Australia, and the United Kingdom. Theories such as constructivism, adult learning, situated learning and experiential learning, as well as methodological approaches like problem-based learning and team-based learning, were cited as the theoretical-conceptual and methodological assumptions. In conclusion, the research reveals the importance of integrating learning theories into IPE in order to improve collaborative training and align educational practice with the needs of the health services. The results reinforce the role of IPE in promoting effective interprofessional practices, introducing students to the reality of health work.
Theoretical, conceptual, and methodological principles of interprofessional health education: a scoping review
Keywords: Educação Interprofissional; Relações Interprofissionais; Revisão de Escopo; Equipe de Saúde; Interprofessional education; Interprofessional relations; Scoping review; Healthcare Teams; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS DA SAUDE; 4. Educação de Qualidade